Inequalities in British University League Tables: The Covid-19 Pandemic and Halo Effects (International Journal of Multidisciplinary Perspectives in Higher Education, 2021)
This essay explores the impact of the Covid-19 pandemic on the position of British universities in league tables. We argue that the pandemic has increased the inequalities between universities. Through the analysis of the three core functions of universities – research, internationalization, and teaching, we predict that the gap between top-tier and second-tier universities will widen, mainly due to the former’s halo effect.